2020
DOI: 10.3390/ma13235575
|View full text |Cite
|
Sign up to set email alerts
|

Production of Greener High-Strength Concrete Using Russian Quartz Sandstone Mine Waste Aggregates

Abstract: Quartz sandstone (QS) is a mine waste; therefore, its use in construction allows for both reducing the cost of the concrete and contributing to the utilization of waste. The scientific originality of this study is the identification of models of the effect of QS aggregate on the physicomechanical, durability characteristics, and eco-safety of greener high-strength concrete. The study used an energy-efficient method of non-thermal effects of electromagnetic pulses on the destruction mechanisms of quartz-contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 25 publications
0
29
0
3
Order By: Relevance
“…Thus, curing is an essential step; that is, AAM pastes must be reserved within a sensible moisture and temperature range. Extending curing time endorses creating a cross-linked binding and a dense microstructure [ 133 , 197 ] as curing temperatures rise from 30 to 50 °C, the reactivity of FA increases. Furthermore, when curing temperatures are limited within the range of 60 and 90 °C, the geopolymerization is near complete [ 198 ].…”
Section: Fresh State Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, curing is an essential step; that is, AAM pastes must be reserved within a sensible moisture and temperature range. Extending curing time endorses creating a cross-linked binding and a dense microstructure [ 133 , 197 ] as curing temperatures rise from 30 to 50 °C, the reactivity of FA increases. Furthermore, when curing temperatures are limited within the range of 60 and 90 °C, the geopolymerization is near complete [ 198 ].…”
Section: Fresh State Propertiesmentioning
confidence: 99%
“…The optimum compressive strength was 93 MPa [ 189 ]. In a previous study [ 241 ], recycled coarse aggregate (RCA) obtained from crushed structural concrete beams and clay was utilized in FA-based AAM to produce concrete with adequate mechanical characteristics [ 197 , 241 , 242 , 243 ]. It was reported that AAM with RCA developed a less compressive strengths of up to 10.3 MPa compared to that with natural coarse aggregates [ 241 ].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The related literature on this topic also shows the flexibility and importance of choosing scenarios for the respective studies and border systems. Most studies clearly define the objective and scope of the study, making it easier for readers to understand the different criteria considered in each of them, such as [63][64][65][66][67][68][69][70][71][72] (Figure 8), [65][66][67][68][69][70][71][72][73][74] (Figure 9), and [66][67][68] (Figure 10). In civil engineering, the lifecycle assessment in elements, such as walls, with different end-of-life potentials, is mainly related to direct reuse residues or demolition processes, which depends on the users.…”
Section: Sustainability In Civil Engineering Through the Lifecycle Assessment (Lca) Using Petmentioning
confidence: 99%
“…Several factors affect the concrete thermal conductivity [55]. For instance, the type of aggregate [56,57], the properties of cementitious materials [58][59][60][61][62][63][64][65][66], moisture content [67,68], design buildup [69][70][71][72][73][74], temperature [75,76], concrete density [12,[77][78][79][80], etc. The measurement of concrete thermal conduction is divided into steady-state and transient methods [81].…”
Section: Thermal Conductivitymentioning
confidence: 99%